PROBLEMS FACED IN TRANSLATING PROPER NOUNS - Abdikhamidova, Sevinch (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Translating proper nouns is a complex aspect of literary translation, influenced by diverse interpretations. This article examines the challenges and strategies involved, highlighting the significance of proper nouns in literature. It aims to identify the best translation approach for our examples.